Unusual Electrical and Magnetic Properties in Layered EuZn2As2. Issue 6 (12th April 2022) - Blawat, Joanna; Marshall, Madalynn; Singleton, John; Feng, Erxi; Cao, Huibo; Xie, Weiwei; Jin, Rongying
Abstract: Eu‐based compounds often exhibit unusual magnetism, which is critical for nontrivial topological properties seen in materials such as EuCd2 As2 . The authors investigate the structure and physical properties of EuZn2 As2 through measurements of the electrical resistivity, Hall effect, magnetization, and neutron diffraction. Their data show that EuZn2 As2 orders antiferromagnetically with an A‐type spin configuration below T N = 19 K. Surprisingly, there is strong evidence for dominant ferromagnetic fluctuations above T N, as reflected by positive Curie–Weiss temperature and extremely large negative magnetoresistance (MR) between T N and T fl ≈200 K. Furthermore, the angle dependence of the MR ab indicates field‐induced spin reorientation from the ab ‐plane to a direction ≈45° from the ab plane. Compared to EuCd2 As2, the doubled T N and T fl make EuZn2 As2 a better platform for exploring nontrivial magnetic and electronic properties in both magnetic fluctuation ( T N < T < T fl ) and ordered ( T < T N ) regimes. Abstract : EuZn2 As2 orders in an A‐type antiferromagnetic structure below T N = 19 K with strong evidence for dominant ferromagnetic (FM) fluctuation between T N and T fl ≈200 K. It is an excellent platform for exploring topological properties in both the FM fluctuation and antiferromagnetically ordered regime, which is extremely important for understanding the interplay between magnetism and nontrivial topology.